Postoperative pain: knowledge and beliefs of patients and nurses. Issue 21 (27th March 2017) - van Dijk, Jacqueline FM; Schuurmans, Marieke J; Alblas, Eva E; Kalkman, Cor J; van Wijck, Albert JM
Abstract : Aims and objectives: To describe patients' and nurses' knowledge and beliefs regarding pain management. Moreover, to explore the effect of information and education on patients' and nurses' knowledge and beliefs regarding pain management. Background: In the treatment of postoperative pain, patients' and nurses' inadequate knowledge and erroneous beliefs may hamper the appropriate use of analgesics. Design: A randomised controlled trial and a cross‐sectional study. Methods: In 2013, half of 760 preoperative patients were allocated to the intervention group and received written information about the complications of postoperative pain. The knowledge and beliefs of 1184 nurses were studied in 2014 in a cross‐sectional study. All data were collected with the same questionnaires. Results: In the intervention group, patients' knowledge level was significant higher than in the control group, while no differences were found in beliefs. Nurses had higher knowledge and more positive beliefs towards pain management compared with both patient groups. Nurses with additional pain education scored better than nurses without additional pain education. Nurses were also asked what percentage of pain scores matched their impression of the patient's pain, and the mean was found to be 63%. Conclusions: Written information was effective for increasing patients' knowledge. However, it was not effective for changing beliefs about analgesics and patients and nurses had erroneous beliefs about analgesics. Relevance to clinical practice: It is necessary to continue to inform patients and nurses about the need for analgesics after surgery. Such education could also emphasise that a discrepancy between a patient's reported pain score and the nurse's own assessment of the patient's pain should prompt a discussion with the patient about his/her pain.